2019
DOI: 10.1108/tqm-12-2018-0208
|View full text |Cite
|
Sign up to set email alerts
|

On the application of Lean principles and practices to innovation management

Abstract: Purpose Increasingly, a firm’s innovation capability has become one of the key frontiers of competitive advantage. The Lean philosophy has a well-proven reputation for its focus on process efficiency and effectiveness, and therefore, is often applied in various areas of innovation. Such wide and ever-increasing applicability also has resulted in an incoherent corpus of literature on Lean innovation. The purpose of this paper is to conceptualize an integrative view on Lean innovation management. Design/method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 124 publications
(177 reference statements)
4
34
0
2
Order By: Relevance
“…Technologies of Industry 4.0 are Cyber Physical System (CPS), Big Data analytics, IoT, IoS and artificial intelligence (AI). Several benefits of integrating lean principles and Industry 4.0 are: enhancement of flexibility of equipment, complex decision-making replaced by real time decision-making, modularization of production system and enhancement of process improvement (Sauter et al , 2016; Rossini et al , 2019; Solaimani et al , 2019). Integration of Industry 4.0 techniques along with lean principles will lead to enhance sustainable performance of organization (Kamble et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Technologies of Industry 4.0 are Cyber Physical System (CPS), Big Data analytics, IoT, IoS and artificial intelligence (AI). Several benefits of integrating lean principles and Industry 4.0 are: enhancement of flexibility of equipment, complex decision-making replaced by real time decision-making, modularization of production system and enhancement of process improvement (Sauter et al , 2016; Rossini et al , 2019; Solaimani et al , 2019). Integration of Industry 4.0 techniques along with lean principles will lead to enhance sustainable performance of organization (Kamble et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results from the literature survey showed that there is an increase in trend for research on integrating CI strategies with I4.0 tools. Enormous benefits can be achieved by integrating CI strategies and I4.0 tools in terms of flexibility of system, enhanced quality performance, modularization of production system, enhancement of process improvement, reduction in production cost and also providing sustainable benefits from TBL viewpoint (Sauter et al , 2016; Kiel et al , 2017; Rossini et al , 2019; Solaimani et al , 2019). After conducting the literature survey, understanding the recent trends and future challenges, discussion with key practitioners and experts, a framework has been developed for integrating Industry 4.0 with CI strategies.…”
Section: Developed Conceptual Frameworkmentioning
confidence: 99%
“…Moreover, a more detailed understanding of the sustainability footprint of hybrid manufacturing workflows (i.e., combining additive and subtractive techniques) is an interesting research direction [67]. Finally, the impact of additive manufacturing on Lean management in achieving higher sustainability performance, in terms of waste minimalization, process flow, quality, and employee's safety, is another potential direction for future research [68][69][70].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Lean has an excellent reputation for its focus on process efficiency and effectiveness. The Lean philosophy provides principles and practices aimed at updating innovation capacity (Solaimani et al 2019). Thus, BPM is also actualized in the Lean philosophy.…”
Section: Bpm As Part Of Qmmentioning
confidence: 99%